Response of transplanted kharif rice to organic liquid formulations in a red and lateritic soil of Jharkhand - Biswas, Saikat; Kumari, Devyani; Thakur, Raghava (ORYZA-An International Journal of Rice, 2023)
To evaluate the influence of organic liquid formulations on transplanted rice, a field experiment was conducted at farm of Divyayan Krishi Vigyan Kendra, Ramakrishna Mission Ashrama, Ranchi, Jharkhand, India during kharif season of 2021 using 6 treatments (Control i.e. water, Panchagavya, Sasyagavya, Amritpani, Jeevamruth and Kunapajala) in four times replicated randomised block design. Results explored that application of Kunapajala @6% at 30 and 60 days after transplanting registered maximum growth (322.5 tillers/m2,103.6 cm plant height, 24.5 leaves/plant, 1475.1 g/m2 dry matter accumulation). Further, Kunapajala spray attained 30.4%, 4.3%, 11.8%, 14.6%, 45.5%, 43.2% and 45.6% higher panicles/m2, panicle length, grains/panicle, test weight, grain yield, straw yield and biological yield of rice, respectively, over control. However, use of Jeevamruth also performed well and remained as second-best option. Kunapajala spray further provided maximum economic profitability (net return of Rs. 83,233/ha and B:C ratio of 3.17) and therefore, it can be recommended for organically kharif rice cultivation.